'Silent' flagellin drives immunotolerance to commensal bacteria. Issue 3 (March 2023) - Xiong, Lifeng; Zhou, Liang
Abstract: Distinguishing between commensal and pathogenic bacteria to generate appropriate responses (tolerance vs. immunogenicity) is a key decision that the human immune system must make to maintain homeostasis. Recently, Clasen and colleagues reported a distinct allosteric interaction between bacterial flagellin and host Toll-like receptor 5 (TLR5), which may shed light on these differences.